2004
DOI: 10.1099/mic.0.26539-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression and complexity of the PRT1 multigene family of Pneumocystis carinii

Abstract: Pneumocystis carinii has a multigene family, PRT1, that encodes proteins with homology to KEX2-like proteases. PRT1 genes cluster with MSG genes near the telomeres and, like MSG, PRT1 proteins seem to be surface-expressed. The clustering of PRT1 and MSG genes suggested that expression of the two multigene families might be coordinated. Studying gene expression in P. carinii has been hampered by the lack of a culture system, and by lack of clonality in P. carinii populations in naturally infected rats, the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…These samples were washed, and RNA was isolated as described. Quantitative PCR was performed to enumerate the P. carinii using the Bio-Rad iCycler with primers to the P. carinii prt1 multigene (spanning P. carinii prot1 and prot3) (61). Amplifications of unknown samples were compared to standard samples containing rat P. carinii prt1 RNA, and the resulting measure of RNA copies was proportioned to the net P. carinii burden (62).…”
Section: Methodsmentioning
confidence: 99%
“…These samples were washed, and RNA was isolated as described. Quantitative PCR was performed to enumerate the P. carinii using the Bio-Rad iCycler with primers to the P. carinii prt1 multigene (spanning P. carinii prot1 and prot3) (61). Amplifications of unknown samples were compared to standard samples containing rat P. carinii prt1 RNA, and the resulting measure of RNA copies was proportioned to the net P. carinii burden (62).…”
Section: Methodsmentioning
confidence: 99%
“…This immune response, either through a direct injury or indirectly via activation of a protease cascade, may have led to the physiologic and morphological changes that we measured. It is also possible that there is a direct effect of the organism itself (e.g., activation of a protease cascade by a P. murina-specific protease [1,3,26,41]). These data strongly support a recent report examining primates infected with simian immunodeficiency virus after prolonged colonization with P. macaca (36).…”
Section: Vol 76 2008mentioning
confidence: 99%
“…Other experimental models were used to address this question. In a transgenic SP-D-overexpression mouse model, which developed PcP after antibody-induced CD4 + -cell depletion and inoculation of P. murina Keely et al 2004, it was observed that both P. murina infection and lung inflammatory changes were increased (Vuk-Pavlovic et al, 2006). With regard with SP-A, in the pulmonary lavage fluid of SP-A deficient mice with corticosteroid-induced PcP were observed higher concentrations of TNF-α, IFN-γ and MIP-2 than in wild-type mice (Linke et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The rats of all groups, except of group 2, were infected by non-surgical endotracheal route with P. carinii organisms (Ambrose et al, 2004) obtained from corticosteroid-treated Wistar rats . Parasite extraction from tissue lung and purification were performed as previously (Aliouat et al, 1993).…”
Section: And Intratracheal Inoculationmentioning
confidence: 99%